New crops, new products - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
It was the wicked uncle of Aladdin, in the Tales of the Arabian Nights, who offered 'new lamps for old'. He wanted to find anancient magic lamp that could give him access to a hoard of treasure for his own personal use. When agricultural...